Zaštita od buke - zvučne barijere - Grubeša, Sanja (Array, 2019)
This paper deals with the issue of noise as an environmental pollutant, and furthermore it suggests possible solutions for this issue. Sound is a form of energy transmitted by sound waves. In general, sounds may be perceived as desirable or undesirable. Sounds which are considered undesirable and unwanted can be observed as noise, however the perception of sound in general is significantly subjective and individual. In particular, one person can perceive a certain sound as pleasant, whereas another could characterize it as annoying, unpleasant, and generally undesirable. This paper explains the term “noise” in detail, noise indicators as numerical values, and the ways noise can have a negative impact on people. Even today, noise pollution is often neglected compared to other environmental pollutions (i.e. water pollution, soil pollution, air pollution etc.). However, exposure to noise has an accumulative character. The consequences are noticeable after a prolonged exposure and can manifest themselves as bad mood, fatigue, insomnia, headache and loss of concentration, thereby having a direct influence on the quality of life. The focus of this paper is traffic noise and acoustical solutions which can reduce it. The dominant part of sound energy produced by traffic is in the middle-frequency range, which coincides with the range of maximum sensitivity of human hearing. When planning a new traffic route the negative influence of noise on people and the environment can be reduced by choosing the route which is remote from populated areas. In cases when the roads are fitted into the existing terrain and near populated areas, they can be equipped with protective noise barriers. The paper gives a detailed explanation on what noise barriers are, and an overview of different types of noise barriers that are currently in use. In addition, the advantages and disadvantages of different types of noise barriers are discussed.